Penambahan ekstrak lamun (Enhalus acoroides) dan gonad bulu babi (Diadema setosum) sebagai formulasi sediaan moisturizer body lotion: Addition of seagrass (Enhalus acoroides) extract and sea urchin (Diadema setosum) gonads as formulation of moisturizer body lotion - Lailatul Badriyah; Eka Nurrahema Ning Asih; Siti Nihayatun Ni’amah; Reza Hidayah Ningrum; Yuniar Mardiyanti; Destin Retno Wulansari (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
The skin is a part of the body that is sensitive to changes in temperature due to indoor and outdoor activities. A moisturizer body lotion made from seagrass and sea urchin gonads is a cosmetic product that can be used to treat dry and flaky skin. The purpose of this study was to determine the optimal formulation of moisturizer body lotion based on the characteristics of physical stability, the relationship between the irritation index and the panelist's preference test results, and the phytochemical content of the moisturizer body lotion made from seagrass (Enhalus acoroides) extract and sea urchin (Deadema setosum) gonads. This study consisted of extract preparation, body lotion preparation without the addition of seagrass extract and sea urchin gonads (control) and with addition (2:1, 1:2, and 3:3), body lotion physical stability test, irritation test, and phytochemical test. The results showed that there were color differences among the four body lotion formulations, namely white (control), celery (2:1), sage (1:2), and olive (3:3), with a distinct blossom odor. The pH range was 6.31-8.05 and its spreadability range was 3.2-6.7 cm. The results of the irritation index test from 32 panelists detected 3% indicating symptoms of irritation and severe edema (swelling), and 1% of the heat sensation index was detected. The highest panelist preference test values for color, aroma, and texture indicators were found in the product without the addition of seagrass extract and sea urchin gonads. Moisturizer body lotion preparations contain alkaloids and tannins. The best formulation is the ratio of seagrass extract to sea urchin gonads of 2:1, which is characterized by a high hedonic test (color), absence of irritation index edema, and feeling of heat.